Investigation into the attitudes of general practitioners in Staffordshire to medical audit. Issue 1 (March 1996) - Chambers, R; Bowyer, S; Campbell, I
Abstract : OBJECTIVES–To investigate the attitudes of general practitioners to medical audit, and any associations between their attitudes and their personal characteristics. DESIGN–Postal questionnaire survey. SETTING –Staffordshire, United Kingdom. SUBJECTS–870 Staffordshire general practitioners. MAIN MEASURES–Agreement or disagreement and associations between the attitudes to 16 statements about audit and the doctors' personal or practice characteristics–namely, sex, number of years since qualification, practice list size, number of partners, and the practices' experience of audit. RESULTS–601 Staffordshire general practitioners (69%) responded. There was most agreement with the statements that audit is time consuming (86%), that ongoing training and education is needed (71%), that there is a compulsion applied on doctors to audit (68%), and that extra resources for audit should be provided by the medical audit advisory group (65%). There was considerable disagreement (53% of general practitioners) with the statement that ¿government policy to expect general practitioners to do audit will enhance the population's health.¿ The median response by the 601 general practitioners was four positive responses out of 14 statements about audit (two of the 16 statements could not be graded positive or negative to audit). Women doctors generally had more positive attitudes towards audit, and so had those working with smaller mean list sizes, those in larger partnerships, and those in practices that had carried out audit for a longer time. CONCLUSIONS–There was a generally negative attitude to medical audit, but it was encouraging that those doctors with the most experience of audit obtained the most job satisfaction from it. IMPLICATIONS–More effort is needed to convince general practitioners of the value of audit. Without this, attempts to involve other members of the primary care team in multidisciplinary clinical audit are unlikely to be effective. Successful audits that are shown to be cost effective as well as leading to improvements in patient care should be publicised and replicated. A higher proportion of resources should be devoted to audit.